Encuentros con la naturaleza y la cultura en América Latina - Casas U., Ronald (2012)
This paper aims to bring a philosophical reflection and analysis to the human encounter with our natural environment, focusing on the Latin American experience. We revise some of the best known theories of latin american thinkers and the methods of native peoples in their relationships to natural environment.